Acupuncture version of breech presentation: a randomized sham-controlled single-blinded trial. (September 2016) - Sananes, Nicolas; Roth, Georges E.; Aissi, Germain A.; Meyer, Nicolas; Bigler, Annick; Bouschbacher, Jean-Michel; Helmlinger, Christine; Viville, Brigitte; Guilpain, Mélanie; Gaudineau, Adrien; Akladios, Chérif Y.; Nisand, Israël; et al.
Abstract: Background: Several studies have investigated the efficacy of moxibustion with or without acupuncture for fetal version, but the results are discordant. Meta-analyses pointed out the need for robust, methodologically sound, randomized controlled trials. Objective: The objective of this study was to assess the effectiveness of acupuncture with fire needling on acupoint BL67 for version of breech presentation. Study design: This was a randomized, sham-controlled, single-blinded trial, which took place in Strasbourg teaching maternity hospital, France. A total of 259 patients between 32 and 34 weeks of gestation have been randomized and analyzed. Patients were randomized to either acupuncture with fire needling or sham group, and were analyzed in their initial allocation group. Statistical analysis was conducted using Bayesian methods, in univariate analysis and in multivariate analysis after adjustment on parity. Results: The primary outcome was the rate of cephalic presentations at ultrasound examination performed between 35 and 36 weeks of gestation. A total of 49 (37.7%) fetuses were in cephalic presentation in the acupuncture group, versus 37 (28.7%) in the sham group: RR 1.34 [0.93–1.89], Pr RR > 1 = 94.3%. After adjustment on parity, the acupuncture did not increase the rate of fetal cephalic version: OR 1.47 [0.84–2.42], Pr OR > 1 = 90.3%. Conclusions: Our study suggests that acupuncture with fire needling on acupoint BL67 does not promote fetal cephalic version. Further studies might investigate effectiveness of other protocols of acupuncture. Randomization should be stratified for nulliparous and parous patients.